Investigating the causal association between branched-chain amino acids and Alzheimer's disease: A bidirectional Mendelian randomized study - Qian, Xiao-hang; Liu, Xiao-li; Zhang, Bin; Lin, Yuan; Xu, Jian-hua; Ding, Gang-yu; Tang, Hui-dong (Frontiers in Nutrition, 2023)
Background: There are many metabolic pathway abnormalities in Alzheimer's disease (AD). Several studies have linked branched-chain amino acids (BCAAs) metabolism disorders with AD, but have not obtained consistent results. The purpose of this study is to explore the causal association between the BCAAs concentration and the risk of AD. Methods: A bidirectional Mendelian randomized (MR) was applied to explore the causal effect between BCAAs level and the risk of AD. Genetic instrumental variables from the genome-wide association study (GWAS) of serum BCAAs levels [total BCAAs (115,047 participants), valine (115,048 participants), leucine (115,074 participants), isoleucine (115,075 participants)] from UK biobank and AD (21,982 AD cases and 41,944 controls) from the International Genomics of Alzheimer's Project) were applied to explore the causal effect through the inverse-variance weighted (IVW) method, MR Egger and Weighted median, accompanied by multiple pluripotency and heterogeneity tests. Results: The forward MR analysis showed that there were not casual effect of total BCAAs (OR: 1.067, 95% CI: 0.838-1.358; p = 0.838), valine (OR: 1.106, 95% CI: 0.917-1.333; p = 0.292), leucine (OR: 1.096, 95% CI: 0.861-1.396; p = 0.659), isoleucine (OR: 1.457, 95% CI: 1.024-2.742; p =0.037) level on the risk of AD. The reverse analysis showed that AD was related with reduced levels of total BCAAs (OR: 0.979, 95% CI: 0.989-0.990; p < 0.001), valine (OR: 0.977, 95% CI: 0.963-0.991; p = 0.001), leucine (OR: 0.983, 95% CI: 0.973-0.994; p = 0.002), isoleucine (OR: 0.982, 95% CI: 0.971-0.992; p = 0.001). Conclusion: We provide robust evidence that AD was associated with a decreased level of BCAAs, which can serve as a marker for early diagnosis of AD.